Acute Myocardial Infarction and Predisposing Risk Factors - Julio Armando Sánchez Delgado; Nailé Edita Sánchez Lara; Yalith Pavón Rodríguez; Zulema Castro Vega (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: more than seven million people die each year as a result of ischemic heart disease. The incidence of risk factors constitutes an overload of activity for the heart, which presupposes an increase in the occurrence of myocardial infarction. Objective: determine the epidemiology of acute myocardial infarction and predisposing risk factors. Method: a descriptive, analytical, longitudinal, retrospective study of a series of cases was carried out from the population with a diagnosis of acute myocardial infarction evaluated in the Medical Emergency Service of the Carlos Enrique Font Banes Clinical Surgical Teaching Hospital, Holguín province during the period May 2022-2023. The universe covered 57 diagnosed individuals. By simple random probabilistic sampling, a sample of 38 cases was obtained. The variables were operationalized: age, sex, type of infarction, risk factors, global cardiovascular risk. The following statisticians were used: Pearson's Chi square, Odd Ratio (OR), including p and confidence interval. Results: the male sex prevailed in 63.1 %. The age group 60-69 years old was the most affected with 31.6 %. Painful acute myocardial infarction was 71.1 % (OR=6), with ST elevation 76.3 % (OR=10.3) and on the posterior side 39.5 % obtained high statistical values. The risk factors, arterial hypertension (X2=25.4 OR=14 95 % CI (4.6; 42.3) and family history of cardiovascular disease (X2=5.2 OR=2.9 95 % CI (1, 1; 7.4)) expressed a highly significant association for acute myocardial infarction. The mean global cardiovascular risk predominated (52.6 % OR=1.23 X2=0.21). Conclusions: individuals with acute myocardial infarction show an average global cardiovascular risk at the expense of preventable risk factors.